Interchanging : future designs for responsive transport environments - Gardner, Nicole; Haeusler, M. Hank; Mahar, Briedy ([Baunach, Germany] : AADR, 2014)
With consideration of a range of social trends, but also emerging responsive and sustainable technologies, the essays and design projects presented here reimagine, in various ways, a public transport Interchange of the Future better suited to address the complexities and conditions of 21st century urban digital life.
Interchanging brings together a collection of design projects and interdisciplinary perspectives on policy, planning, design, and management issues, that currently, and are set to, shape and influence our expectations and experiences of urban public transport environments. This comprises a unique range of contributions from academics, industry and practice, including the Australian Research Council Linkage Grant project and research team Encircle: Dr. M. Hank Haeusler (University of New South Wales/ UNSW), Briedy Mahar (UNSW), Tim Tompson (UNSW), Dr. Martin Tomitsch (University of Sydney), Dr. Nathan Kirchner (University of Technology Sydney/UTS) and Dr. Michelle Zeibots (UTS), together with Nicole Gardner (UTS), Tom Hordern (Volvo Group), Transport for New South Wales, Bonnie Parfitt (City of Sydney), Jimmy Ti (Queensland University of Technology/QUT), Professor Alec Tzannes (Tzannes Associates/UNSW), and Mark Gilder (Grimshaw Architects), and with a foreword by Associate Professor Marcus Foth, Director of the Urban Informatics Research Lab at QUT.
CONTEXT : Introduction: responsive transport environments -- Interdisciplinary framework -- VISION: Urban infostructures of possibility -- Reframing public transport: what is and what ifs? -- Future transport services: challenges and opportunities -- PARAMETERS: NSW long term transport master plan -- The role of the City of Sydney in bus shelter provision -- Responsive passenger information systems: the next generation -- STUDIO: Nexus -- Givetakegive -- Growth -- Refuel -- Active -- SYSTEMS: Urban informatics in public transport environments -- Sense and sensing in public transport environments -- The history and future of interaction design in public trasport environments -- COMPONENTS: Designing urban infrastructure -- Designing public transport -- Enabling new revenue models through media architecture -- SITUATING: Interchange of the future.
Includes bibliographical references.
Keywords: Transportation -- Planning; Urban transportation -- Planning; Local transit -- Planning